Holistic health and social care outreach for people experiencing homelessness with recent non-fatal overdose in Glasgow, Scotland: the Pharmacist and third sector Homeless charity worker Outreach Engagement Non-medical Independent prescriber Rx (PHOENIx) pilot randomised controlled trial - Vibhu Paudyal; Nicola Greenlaw; Frances S Mair; Kate Stock; Andrew McPherson; Andrea E Williamson; Richard Lowrie; Donogh Maguire; Steven Ross; James Roy Robertson; Alison Boyle; Clare Duncan; et al. (BMJ Public Health)
Objectives To examine randomised controlled trial (RCT) progression criteria including emergency department (ED) attendance and non-fatal overdose, from a holistic, integrated health and social care outreach intervention (PHOENIx), for people experiencing homelessness with recent non-fatal street drug overdose.Design Pilot RCT. 1:1 randomisation to PHOENIx plus usual care (UC) or UC.Setting Glasgow, Scotland.Participants 128 adults experiencing homelessness with at least one non-fatal street drug overdose in the preceding 6 months.Interventions Pharmacists from the National Health Service and third sector homelessness workers offered weekly outreach. PHOENIx teams develop therapeutic relationships to address health (physical health, mental health and problem drug use) and social care (housing, welfare benefits and social prescribing) in addition to UC. UC comprised building-based primary and secondary health, social and third sector services.Outcomes Primary: progression criteria: recruitment (≥100 participants in 4 months); ≥80% of participants with data collected at baseline, 6 and 9 months; ≥60% of participants retained in the trial at each follow-up period (6 and 9 months); ≥60% of participants receiving the intervention weekly; any reduction in the rate of presentation to ED and overdoses, at 6- or 9-month follow-up. Secondary: participants with, and time to: hospitalisations; health-related quality of life (QoL); treatment uptake for physical and mental health conditions, and problematic drug use.Results Progression criteria were exceeded. In PHOENIx compared with UC, there appeared to be a delay in the median time to ED visit, overdose and hospitalisation but no improvement in number of participants with ED visits, overdoses or hospitalisations. QoL and treatment uptake appeared to be higher in PHOENIx versus UC at 6 and 9 months.Conclusions A definitive RCT is merited, to assess the impact of PHOENIx on people with multiple, severe disadvantages.Trial registration number ISRCTN10585019.